MENINGKATKAN KEAKTIFAN SISWA DALAM MENGIKUTI LAYANAN BIMBINGAN DAN KONSELING DENGAN MEDIA TELEGRAM - SITI KHORIYATUN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This action research was motivated by the fact that the face-to-face hour load in the madrasah curriculum was 53 hours per week, which closed the possibility for Guidance and Counseling teachers to enter class. This has an impact on the inactivity of students in participating in Guidance and Counseling services at madrasas, therefore it is necessary to innovate so that students can receive classical guidance services without face-to-face, namely by using telegram media which is expected to increase student activity in participating in Guidance and Guidance services. counseling. The application of this media is carried out in class 11 MIPA 2 MAN 1 Gunungkidul for the 2021/2022 academic year. By using telegram media students can learn happily, students respond well and students understand the material more easily and students have their own room to carry out personal guidance/consultation. There is an increase in student activity in participating in service activities by opening, reading and commenting in group notes and also being able to do private notes. Based on the research, students opened, read and commented on telegram chat in cycle 1 by 10% and in cycle 2 it increased to 60%. Students open and read the contents of telegram posts and respond briefly or by sending emojis in cycle 1 by 15% and in cycle 2 it increases to 30%. Students only open and read chat telegrams from the BK teacher in cycle 1 by 25% and in cycle 2 it drops to 10%. Students do not open telegram chat in cycle 1 by 50% and in cycle 2 it drops to 10%. From these data it can be concluded that tellegram media can increase student activity in participating in Guidance and Counseling service activities. ABSTRAKPenelitian tindakan ini di latar belakangi oleh suatu kenyataan bahwa beban jam tatap muka dalam kurikulum madrasah 53 jam per minggu sehingga menutup kemungkinan untuk guru Bimbingan dan Konseling bisa masuk ke kelas. Hal ini berimbas pada kurang aktifnya siswa dalam mengikuti layanan Bimbingan dan Konseling di madrasah, maka dari itu perlu dilakukan inovasi agar siswa bisa menerima layanan bimbingan klasikal tanpa melakukan tatap muka yaitu dengan menggunakan media telegram yang di harapkan bisa meningkatkan keaktifan siswa dalam mengikuti layanan Bimbingan dan konseling. Penerapan media ini dilaksanakan di kelas 11 MIPA 2 MAN 1 Gunungkidul tahun pelajaran 2021/2022. Dengan menggunakan media telegram siswa bisa belajar dengan senang, siswa merespon dengan baik dan siswa lebih mudah memahami materi serta siswa mempunyai ruangan tersendiri untuk melakukakan bimbingan/konsultasi secara pribadi. Adanya peningkatan keaktifan siswa dalam mengikuti kegiatan layanan dengan membuka, membaca dan berkomentar dalam cattingan group dan juga bisa melakukakn catting pribadi. Berdasarkan penelitian Siswa membuka , membaca dan berkomentar dalam chat telegram dalam siklus 1 sebesar 10 % dan di siklus 2 meningkat menjadi 60 %. Siswa membuka dan membaca isi kiriman telegram serta menanggapi dengan singkat atau dengan kirim emoji pada siklus 1 sebesar 15 % dan pada siklus 2 meningkat menjadi 30 %. Siswa hanya membuka dan membaca chat telegram dari Guru BK pada siklus 1 sebesar 25 % dan pada siklus 2 turun menjadi 10 %. Siswa tidak membuka chat telegram pada siklus 1 sebesar 50 % dan pada siklus 2 turun menjadi 10 %. Dari data tersebut diperoleh kesimpulan bahwa media tellegram dapat meningkatkan keaktifan siswa dalam mengikuti kegiatan layanan Bimbingan dan Konseling .